(untitled) (Ameghiniana, 2014)
Monticulipora argentina was erected by Kayser to include a conical form composed by smalllongitudinal tubes, found in the Early Ordovician limestone of the San Juan Formation, Argentine Precordillera. For more than a hundred years M. argentina was regarded as a bryozoan species. Recently,M. argentina was excluded from the Phylum Bryozoa, erecting the new genus Fiscella of uncertain affinities. Two different forms were recognized: Fiscella argentina (Kayser) and Fiscella jlabelis Carrera. The possible relationship of these organisms with aseptate corals, calcareous algae or gastropod opercula was suggested. Newly discovered material and recentiY published papers allow the taxonomic assignment of these forms to gastropod opercula. Teiichispira argentina (Kayser) is a new combination for Fiscella argentina (Kayser), and the species is transferred to the gastropod genus Teiichispira Yochelson and Jones. Fiscella jlabelis Carrera is an operculum of a macluritacean gastropod. No gastropod shells of the appropriate size and shape which might correspond to the two opercula were found in the same beds. The paleobiogeographic distribution of Teiichispira is restricted to tropical areas as suggested by the paleogeographic position of the localities where this genus was recorded.